P3.415 Concurrency & Seromixing Among MSM with Recent HIV Infection and New HIV Diagnosis: Implications For PrEP. (13th July 2013) - Gorbach, P M; Pines, H A; Javanbakht, M; Bolan, R; Weiss, R E
Abstract : Background: Understanding the frequency of concurrent sexual partnerships, especially with HIV-positive partners, can guide prevention strategies such as pre-exposure prophylaxis (PrEP) for HIV-negative men who have sex with men (MSM). Methods: From 2009–2012, 295 MSM testing for HIV in Los Angeles reported up to 6 male sex partners via computer-assisted self-interviews. Concurrency was defined as overlapping dates of sexual partnerships. Nucleic acid amplification tests and detuned assays were performed to determine recent and longstanding HIV infections. Associations between HIV status (recent, longstanding, or negative) and partnership type, concurrency, and serostatus of partners were examined using multinomial logistic regression. Results: Participants were diverse (14.5% African-American, 27.0% White, 51.2% Latino), with mean age of 29.9 years (SD = 8.0); 42.0% had recent infection, 27.7% longstanding infection, and 36.6% were HIV-negative. 55.5% reported concurrent partnerships. Of the 887 partnerships reported, 30.6% (265/866) were main partnerships. Among main partnerships with HIV-negative partners, 47.8% (77/161) had ≥ 1 concurrent partner; of those 47.2% (34/72) included ≥ 1 HIV-positive/status unknown concurrent partner. In main partnerships with HIV-positive/status unknown partners, 55.1% (38/69) had ≥ 1 concurrent partner and of those 65.7% (23/35) had ≥ 1 HIV-positive/status unknown concurrent partner. Adjusting for age and race, compared to HIV-negative testers, having recent infection was associated with substance use (adjusted odds ratio [AOR] = 1.99, 95% CI: 1.03–3.85) and concurrency (AOR = 1.88, 95% CI: 1.05–3.39); having longstanding infection was associated with no main partner (AOR = 2.27, 95% CI: 1.00–5.16) or ≥ 1 HIV-positive/status unknown main partner (AOR = 3.63, 95% CI: 1.42–9.30) compared to having only HIV-negative main partners, but not with concurrency. Conclusion: The findings associating concurrency with recent infection indicate a broad need for PrEP by MSM with main HIV positive and HIV negative partners. For MSM exposure to HIV may be occurring from concurrent outside partners suggesting a need for PrEP for partnered and non-partnered MSM.